(untitled) (Research, Society and Development, 2022)
Objective: To develop a protocol for the care of pediatric patients in Cardiorespiratory Arrest in a pediatric hospital in Fortaleza. Methodology: a methodological study. In the first stage, an integrative review was carried out with a search in the Pubmed/Medline, Latin American and Caribbean Literature in Health Sciences databases (LILACS); Scientific Electronic Library Online (SCIELO), and Google Scholar with the descriptors "cardiopulmonary resuscitation", "pediatrics" and "rapid response team", with a final sample of 08 scientific articles. The second stage was the preparation of the proposed protocol. Results: sample showed that the pediatric public, before evolving to a cardiorespiratory arrest event begins to present changes in vital signs and warning of physiological decline a few hours before the event itself, around 3 to 11 hours, and enters the main positive skills/characteristics, cited as necessary to professionals involved in cardiopulmonary resuscitation, are: communication (41%), experience (25%), proactivity (17%) and confidence (17%). Conclusion: the study has implications for clinical practice, such as defining specific functions for professionals involved in cardiopulmonary resuscitation, outside the intensive care and emergency environment, highlighting the main problematic points, thus pointing out opportunities for improvement and alignment of the performance of all professionals.